Pneumatic Control System of Automatic Production Line Using Two Method of SCADA/HMI Implement PLC - hadi, hala helal; Salloom, Maher Yahya (Al-Khwarizmi Engineering Journal, 2019)
This work focuses on the implementation of interfaces for human machine interaction (HMI) for control and monitor of automatic production line. The automatic production line which can performance feeding, transportation, sorting functions.                  The objectives of this work are implemented two SCADA/HMI system using two different software. TIA portal software was used to build HMI, alarm, and trends in touch panel which are helped the operator to control and monitor the production line. LabVIEW software was used to build HMI and trends on the computer screen and was linked with Microsoft Excel (ME) to generate information table which are helped to monitor the performance of the pneumatic equipment.      As a result, the realized system enables two human interfaces for controlling and monitoring the physical values of the pneumatic system processes and parameters, and it provides a way for different software packages to access values from control device (PLC) which helps to monitor the performance of the pneumatic equipment.          The implemented system can be used in the laboratory for reducing the distance between theoretical knowledge and practical applications for engineering students, it will play a significant role in developing the ability of innovation and practical application. Also, the implemented system of the production line is a prototype with an actual production situation which is very close to the actual environment control process in the factory.